Biological peculiarities of pikeperch (Sander lucioperca Linnaeus, 1758) as a promising object of freshwater aquaculture of Ukraine (a review) - O. Polishchuk; M. Simon (Ribogospodarsʹka Nauka Ukraïni, 2023)
Purpose. Nowadays, pikepersh (Sander lucioperca Linnaeus, 1758) is currently one of the most popular fish among both consumers and producers of quaculture products, which attracts the attention of scientists who are constantly improving technologies for working with it. That's why, our goal was to analyse a selection of professional literary sources from different years and, based on their analysis, to provide a brief review of the main commercially valuable features of a species of the native ichthyofauna of Ukraine — pikepersh. To review the modern problems about the existence of populations of this species in various water bodies and ways of solving them as well as the prospects of its cultivation in the conditions of modern Ukraine.